2015
DOI: 10.1108/ijbm-11-2014-0168
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of long-term savings behavior from the consumers’ perspective

Abstract: Purpose – The purpose of this paper is to delineate the impact of social context and savings attitudes on consumers’ self-reported long-term savings and discuss how these drivers can be influenced to increase an individual’s savings rate. Design/methodology/approach – An online survey was conducted among 993 German savers. A structural equation model quantified the influence of the social context and an individual’s attitudes on long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…As a result, the intention to save depicts an important process to final saving behaviour (Ruefenacht et al, 2015). In several TPB studies, behavioural intention is considered as a proxy measure of likely behaviour (e.g., Phillips & Jang, 2012;Sparks & Pan, 2009;Wang & Ritchie, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the intention to save depicts an important process to final saving behaviour (Ruefenacht et al, 2015). In several TPB studies, behavioural intention is considered as a proxy measure of likely behaviour (e.g., Phillips & Jang, 2012;Sparks & Pan, 2009;Wang & Ritchie, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The result also reveals that there is a positive relationship between interest rate and savings rate. In a rather limited study conducted only in Germany Ruefenacht, Schlager, Maas, and Puustinen (2015) documented perceived importance of societal norms to have a positive influence on savings attitudes among the 3,800 individual respondents in the 16 states of the country.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study by Ruefenacht, Schlager, Maas, and Puustinen (2015), societal norms and values -defined as the interaction between the individual and his or her environment, friends and family -were discovered to influence long-term savings attitudes on individual consumers. The authors drew this conclusion based on 3,800 filled-out surveys returned by targeted respondents in 16 states of Germany.…”
Section: Methodology and Hypothesis Developmentmentioning
confidence: 99%
“…Bandura (1982) explained that efficacy involves a generative capability in which cognitive, social, and behavioural skills components are to be integrated to serve innumerable purposes. Based on the review of past literatures, this study found five theories that were recommended in financial decision-making which are individual characteristics (Gutter & Copur, 2011;Hullgren & Soderberg, 2013), self-efficacy (Farrel et al, 2016), cognitive (Boyle et al, 2013;Estelami, 2009;Okonkwo, Wadley, Griffith, Ball, & Marson, 2006), socialisation (Hira et al, 2013;Shim, Barber, Card, Xiao, & Serido, 2010;Ruefenacht et al, 2015), and religious faith (Baxomusa & Jalal, 2014;Keister, 2008).…”
Section: Literature Review Theoretical Backgroundmentioning
confidence: 99%
“…Despite, very little attention has been given to household micro-data with detailed household characteristics in past literature (Abildgren, 2016;Ruefenacht, Schlager, Mass, & Puustinen, 2015). The life-cycle model had been widely used in past literature in understanding private saving (Ruefenacht et al, 2015), however, life-cycle model at times failed to explain aspects of private saving (Brounen et al, 2016;Eriksson & Hermansson, 2014;Jan & Lin, 2014;Lown, Kim, Gutter, & Hunt, 2015). Thus, more theories had been adopted in past literature to understand private saving beyond life-cycle model.…”
Section: Introductionmentioning
confidence: 99%